Diachronous retreat of the Greenland ice sheet during the last deglaciation. (1st August 2016) - Sinclair, G.; Carlson, A.E.; Mix, A.C.; Lecavalier, B.S.; Milne, G.; Mathias, A.; Buizert, C.; DeConto, R.
Abstract: The last deglaciation is the most recent interval of large-scale climate change that drove the Greenland ice sheet from continental shelf to within its present extent. Here, we use a database of 645 published 10 Be ages from Greenland to document the spatial and temporal patterns of retreat of the Greenland ice sheet during the last deglaciation. Following initial retreat of its marine margins, most land-based deglaciation occurred in Greenland following the end of the Younger Dryas cold period (12.9–11.7 ka). However, deglaciation in east Greenland peaked significantly earlier (13.0–11.5 ka) than that in south Greenland (11.0–10 ka) or west Greenland (10.5–7.0 ka). The terrestrial deglaciation of east and south Greenland coincide with adjacent ocean warming. 14 C ages and a recent ice-sheet model reconstruction do not capture this progression of terrestrial deglacial ages from east to west Greenland, showing deglaciation occurring later than observed in 10 Be ages. This model-data misfit likely reflects the absence of realistic ice-ocean interactions. We suggest that oceanic changes may have played an important role in driving the spatial-temporal ice-retreat pattern evident in the 10 Be data. Highlights: 645 published 10 Be ages and 791 14 C ages from around the Greenland ice sheet. Analyze 10 Be and 14 C database using factor analysis to identify spatial patterns. 10 Be ages show diachronous terrestrial retreat of Greenland Ice Sheet. This spatial pattern is not observed in 14 C ages or an ice sheet model.